2015
DOI: 10.1128/jcm.03609-14
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effective Pooling of DNA from Nasopharyngeal Swab Samples for Large-Scale Detection of Bacteria by Real-Time PCR

Abstract: We investigated the potential of pooling DNA from nasopharyngeal specimens to reduce the cost of real-time PCR (RT-PCR) for bacterial detection. Lyophilization is required to reconcentrate DNA. This strategy yields a high specificity (86%) and a high sensitivity (96%). We estimate that compared to individual testing, 37% fewer RT-PCR tests are needed. R eal-time PCR (RT-PCR) is an essential tool for routine diagnostics and large epidemiological studies of infectious diseases (1, 2). However, its cost remains s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…Following the proof of theorem 3 in the work of Wang et al, 41 one can show that, with the optimal ( 1 , 2 ) from (8), pr( 1, =  1 , 2, =  2 ) → 1 as N → ∞. In other words, any ( 1 , 2 ) that does not lead to the correct variable selection cannot be selected by (8) when the number of individuals is large. The purpose of this subsection is to provide a shrinkage estimator of the regression coefficients, of which the sparsity pattern can help us identify the truly relevant risk factor for each infection.…”
Section: Variable Selection For Each Infectionmentioning
confidence: 90%
See 1 more Smart Citation
“…Following the proof of theorem 3 in the work of Wang et al, 41 one can show that, with the optimal ( 1 , 2 ) from (8), pr( 1, =  1 , 2, =  2 ) → 1 as N → ∞. In other words, any ( 1 , 2 ) that does not lead to the correct variable selection cannot be selected by (8) when the number of individuals is large. The purpose of this subsection is to provide a shrinkage estimator of the regression coefficients, of which the sparsity pattern can help us identify the truly relevant risk factor for each infection.…”
Section: Variable Selection For Each Infectionmentioning
confidence: 90%
“…Pooled testing (also known as group testing) was initially proposed to screen for syphilis among War World II American army recruits . Since this seminal work, pooling techniques have been successfully implemented to screen for many other infectious diseases, including HIV, hepatitis B virus (HBV), hepatitis C virus (HCV), influenza, and herpes . Besides disease screening, many other areas, including genetics, veterinary science, medical entomology, blood safety, and drug discovery, have also used the method of pooling.…”
Section: Introductionmentioning
confidence: 99%
“…Dorfman is usually credited with its introduction, having proposed it to screen US soldiers for syphilis during World War II. Now widely regarded for its cost‐savings potential, group testing is commonly used in large‐scale sexually transmitted disease screening applications involving HIV, HBV/HCV,() chlamydia and gonorrhea, and for other infections including West Nile virus and influenza . Pooling individuals arises more generally in environmental monitoring, entomology, genetics, animal testing, drug discovery, and food safety …”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity at various group sizes is crucial for determining whether group testing is desirable and for estimating optimal group size. This can be informed by evaluating the effect of pooling one infected specimen with a varying number of uninfected specimens on the sensitivity and cycle threshold (Ct) values [18,21] and mathematical models taking into account viral load progression and dilution effects [22]. Early results from laboratory experiments suggest that a single positive SARS-CoV-2 sample can be detected in pools of up to 32 samples, with an estimated false negative rate of 10% [16].…”
mentioning
confidence: 99%
“…However, because group testing potentially requires fewer tests to be performed, average time delays may actually be reduced, especially in a pandemic setting where laboratories are working at full capacity. For example, a study from France found that, compared with individual testing, pooling deoxyribonucleic acid (DNA) from nasopharyngeal specimens, and retesting positive group samples, considerably reduced both the cost and time delays of using RT-PCR for bacterial detection [21].…”
mentioning
confidence: 99%